Link Budget Analysis of Low Earth Orbit Satellites Considering Antenna Patterns and Wave Propagation in Interference Situations - Kang, Eunjung; Shin, Wookhyeon; Park, Youngju; Park, Yong Bae; Kim, Junghoon; Choo, Hosung (2022 International Symposium on Antennas and Propagation, ISAP 2022, 2022)
This paper proposes a link budget of the high-speed data communication for Low Earth Orbit (LEO) satellites in interference situations. A choke ring horn type antenna with a diameter of 77.4 mm is used as the transmitting antenna in the LEO satellite, which has a half power beam width (HPBW) of 103.2° and a maximum gain of 6.6 dBi at 8 GHz. The receiving antenna in the ground station is a parabolic type of antenna with a diameter of 11.3 m, and it has a HPBW of 0.2° with a maximum gain of 59 dBi at 8 GHz. The J/S is calculated when an unwanted interference source at altitude of 18 km and θj of 0° to 90° moves over the ground station. For J/S of 0 dB, the unwanted power of the elevation angle θj is 89 dBm (θj = 88.1°) and 80.2 dBm (θj = 89.7°).
Keywords: Ground stations; Half power beam widths; High-speed data communication; Interference situation; Interference sources; J/S; Link budget analysis; Link budgets; Low earth orbit satellites; Unwanted interference source; antenna patterns; interference situation; J/S; LEO satellite; link budget; unwanted interference source; wave propagation